The Impact of Macroeconomics and Gold Prices on the IDX Composite Index 2017-2021 - Fatchur Rohman; Luqman Obby Rival (Jurnal Akuntansi dan Perpajakan, 2022)
The existence of a capital market in a country is a benchmark for economic progress and as a support for the economy or the dynamics of a country's business. This research problem is how the impact of Inflation, Interest Rates, Exchange Rates and Gold Prices on IDX Composite Index (ICI). The purpose of this study was to determine how the effect of inflation, interest rates, exchange rates and gold prices on ICI. The type of research used in this research is quantitative research. The independent and dependent variable data taken are closing price data at the end of the month. The data used is secondary data with data collection methods, namely documentation. The sampling method used is the saturated sample method with a total of 60 samples obtained. The data analysis tool used in this study is multiple linear regression using the SPSS program. Based on the data analysis that has been carried out, it can be concluded that the results of the t-test Inflation (X1) have a significant effect on the IDX Composite Index (Y). Interest Rate (X2) has no effect on the IDX Composite Index (Y). The Exchange Rate (X3) has no effect on the IDX Composite Index (Y). Gold Price (X4) has a significant effect on the IDX Composite Index (Y).